The impact of forensic investigations following assisted suicide on post-traumatic stress disorder (Swiss Medical Weekly, 2011)
In Switzerland, all deaths through assisted suicide are reported as unnatural deaths and investigated by a forensic team (police, medical examiner, and state attorney). However, there is limited knowledge concerning the impact these forensic investigations have on the development of post-traumatic stress disorder, complicated grief, or depression in those who have lost a loved one. A cross-sectional survey of 85 family members or close friends who were present at an assisted suicide was conducted in December 2007. The Impact of Event Scale, Inventory of Complicated Grief, and Brief Symptom Inventory were used to assess mental health. The newly developed Forensic Investigation Experience Scale measured the emotional experience of the legal investigation at the death scene. The data suggest that the diagnosis of post-traumatic stress disorder is significantly related to having experienced the forensic investigation as emotionally difficult. Thus, the way the forensic investigation is conducted immediately after an unnatural death is evidently associated with the development of post-traumatic stress. It is recommended that a protocol be developed establishing a standardised response to cases of assisted suicide and that specific training be provided for the legal professionals involved.